Аналіз недоліків законодавства України у сфері захисту персональних даних - Цвірюк, Д. В.; Tsviriuk, D. V. (Право і безпека. - 2013. - № 4 (51). - С. 58-64, 2013)
Розглянуто основні недоліки законодавства України у сфері захисту персональних даних та шляхи вдосконалення засобів правового регулювання сфери захисту інформації про особу. Досліджено окремі види інформації про особу, що віднесені до категорії персональних даних, та сформульовано пропозиції щодо віднесення до цієї категорії інших видів інформації.

Peculiarities of normative and legal consolidation of the concept and content of personal data in the legislation of Ukraine and European Union are the subject of the research. The objective of the article is to analyze international normative and legal acts concerning the category «personal data»; to define peculiarities of fixing the list of personal data in Ukrainian legislation; to analyze some types of information classified as personal data and to improve the list of personal data; to develop own definition of «personal data. The author used a method of analysis and synthesis, as well as comparative and formal and logical methods while this research. These methods allowed the author to analyze international experience and find out that a personality having mental and physiological characteristics of the individual, but not a person as it is in Ukraine is the basis of personal data protection in the countries of EU. This allowed the author to single out two groups of individuals as subjects of personal data: identified and not identified. The author analyzed the definition «personal data» in the Law of Ukraine «On Personal Data Protection» and in the Law of Ukraine «On Information». Special attention is paid to the study of such types of information, related to personal data, as person’s nationality, date and place of birth, health state, information about education, information about a person’s religious beliefs. The author expressed doubts about the feasibility to include information about the nationality and religious beliefs to personal data because this information is not used in public administration sphere. The author suggested to include information about person’s financial condition and bank accounts, as well as information about the person’s ownership of movable and immovable property into the list of personal data. Own definition of «personal data» in the broad and narrow sense is offered. The result of the research is to determine the main shortcomings of Ukrainian legislation in the sphere of personal data protection, namely: the existence of disagreements in normative and legal consolidation of the concept «personal data», the absence of the list of personal data in the Law of Ukraine «On Personal Data Protection».

Рассмотрены основные недостатки законодательства Украины в сфере защиты персональных данных и пути усовершенствования способов правового регулирования сферы защиты информации о личности. Исследованы отдельные виды информации о личности, относящиеся к категории персональных данных, и сформулированы предложения касательно отнесения к этой категории иных видов информации.
Analysis of Ukrainian legislation’s shortcomings in the field of personal data protection
Анализ недостатков законодательства Украины в сфере защиты персональных данных
Keywords: інформація; information; информация; персональні дані; personal data; персональные данные; захист персональних даних; protection of personal data; защита персональных данных; правове регулювання; legal regulation; правовое регулирование; законодавство; legislation; законодательство